The Association Between Personality Traits and eSports Performance - Matuszewski, Piotr; Dobrowolski, Paweł; Zawadzki, Bogdan (Frontiers in Psychology, 2020)
This study focuses on the relationship between personality traits, derived from the Big Five model, and performance in the competitive eSports video game League of Legends. Data were gathered from 206 League of Legends players of various in-game success levels, as measured by their position within the competitive hierarchy (division) of the video game. The NEO-FFI questionnaire was used to measure personality traits within the gathered sample, which was divided into two groups of higher and lower ranked players. The results indicate that players who reach higher divisions in League of Legends tend to be less extraverted, less agreeable, but more open to experience. To our knowledge this is the first report of a link between eSports performance and personality traits. The results are discussed within the context of available knowledge on personality and traditional competitive sports performance.